Postoperative quality of life after laparoscopy‐assisted pylorus‐preserving gastrectomy compared with laparoscopy‐assisted distal gastrectomy for early gastric cancer. Issue 10 (11th February 2020) - Huang, Chen; Yu, Fengrong; Zhao, Gang; Xia, Xiang
Abstract: Background and Aim: This study aimed to investigate the postoperative quality of life (QOL) between laparoscopy‐assisted pylorus‐preserving gastrectomy (LAPPG) and laparoscopy‐assisted distal gastrectomy with Billroth I anastomosis (LADGBI) in patients with middle‐third early gastric cancers (EGC). Methods: From January 2015 to August 2017, a total 91 patients with EGC underwent LAPPG or LADGBI procedure with complete QLQ‐C30 and QLQ‐STO22 in Ren Ji Hospital. Not only do surgical and oncological safety as well as clinicopathologic characteristics analyze, but also chronological changes of QOL and nutritional status were compared for the evaluation of functional advantages. Results: There was no significant difference in clinicopathologic characteristics and perioperative recovery between LAPPG and LADGBI. During postoperative 2‐year follow up, LAPPG showed significant advantages over LADGBI in emotional functioning, insomnia, appetite loss, reflux, and taste problem and presented larger area in global and functional scales and less area in symptom scales, which means that LAPPG tended to present better improvement and less symptoms than LADGBI for QOL 2 years after surgery. Furthermore, LAPPG could bring about significant improvement in total protein and hemoglobin compared to LADGBI at postoperative 2 years. Conclusion: LAPPG obtains QOL as well as total protein and hemoglobin superiority and could be recommended to patients with EGC whose tumor located in the middle third of the stomach.